2008
DOI: 10.3201/eid1411.080532
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Specific Risk Areas forCryptococcus gattii, Vancouver Island, Canada

Abstract: We compared travel histories of case-patients with Cryptococcus gattii infection during 1999-2006 to travel destinations of the general public on Vancouver Island, British Columbia, Canada. Findings validated and refi ned estimates of risk on the basis of place of residence and showed no spatial progression of risk areas on this island over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Molecular analysis established that the isolate was identical to the VGIIa/major genotype responsible for the Vancouver Island outbreak [37] . Additionally, a study from the British Columbia Centre for Disease Control indicated that intra-island travel or tourism on Vancouver Island to highly endemic areas increases the likelihood of contracting cryptococcosis [36] . These studies demonstrate the importance of human travel to endemic areas as it relates to the acquisition and presentation of cryptococcal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular analysis established that the isolate was identical to the VGIIa/major genotype responsible for the Vancouver Island outbreak [37] . Additionally, a study from the British Columbia Centre for Disease Control indicated that intra-island travel or tourism on Vancouver Island to highly endemic areas increases the likelihood of contracting cryptococcosis [36] . These studies demonstrate the importance of human travel to endemic areas as it relates to the acquisition and presentation of cryptococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…While this is the first reported case in the Eastern United States, the suspected ecological niche is in the Western United States, and the patient's travel history is consistent with acquisition in the San Francisco metropolitan area. Travel to endemic areas is known to increase risk for C. gattii exposure and disease, and leads to acquisition in one region with presentation in a distant location [36] , [37] . The Australian case, California transplant patient, and North Carolina patient isolates are closely related to, but not identical at all noncoding genomic markers (VNTR) with Australian environmental isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Public media coverage was less helpful in conveying accurate information [82]. The economic consequences have yet to be tallied, and include the cost of hospitalizations, antifungal medications, and loss of tourism to the area [83]. The value to understanding this novel pathogen, however, has been enormous, as evidenced by the speed with which the genome sequencing has been undertaken by an international consortium of researchers [84].…”
Section: Environmental Aspects Of C Gattiimentioning
confidence: 99%
“…Several reports have documented C. gattii cryptococcosis in visitors to BC and the USPNW [33][34][35][36][37][38]. In February 2007, the first known case of C. gattii infection in North Carolina was reported [37].…”
Section: Travel-associated Infectionmentioning
confidence: 99%